The learning-disabled child - Farnham-Diggory, Sylvia (Harvard University, 1992)
Who is the learning-disabled child? As theories multiply and research accumulates, this pressing question persists, leaving parents and educators and, particularly, students at a loss. \"The Learning-Disabled Child\" aims to provide an answer. A broad-based account of what is currently known and done about learning disabilities, the book gets at the roots of this perplexing problem - and offers a new outlook for its treatment. Since the 1970s, millions of children have been misclassified by public schools as learning-disabled, while many others with true learning disabilities go unidentified and unhelped, as case material presented here makes poignantly clear. Over the same period, research on the nature of learning disabilities, based on samples of misclassified children, has yielded a cloudy and confusing picture. Drawing on her own background in cognitive, developmental and abnormal psychology, as well as her research into reading and dyslexia, Sylvia Farnham-Diggory seeks to cut through the confusion surrounding learning disabilities. She describes advanced research and clinical data that elucidate handicaps in reading, writing and spelling, drawing, calculation, remembering, and problem-solving. In addition, she outlines a straightforward assessment procedure that would reduce the misclassification of learning-disabled children and, if adopted by schools and private diagnostic services, would save the nation billions of misspent dollars. Prescriptive as well as descriptive, \"The Learning-Disabled Child\" offers advice to parents seeking the best methods of diagnostic evaluation, and to teachers in search of the most effective means of helping these children.
Developing child
Keywords: Adolescent; Child; psychologie, klinická psychologie; Infant; dítě; pediatrie; kojenec; poruchy učení; mladiství; Learning Disabilities